If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2+5x)=x=3
We move all terms to the left:
3(2+5x)-(x)=0
We add all the numbers together, and all the variables
3(5x+2)-x=0
We add all the numbers together, and all the variables
-1x+3(5x+2)=0
We multiply parentheses
-1x+15x+6=0
We add all the numbers together, and all the variables
14x+6=0
We move all terms containing x to the left, all other terms to the right
14x=-6
x=-6/14
x=-3/7
| 8(v−87)=96 | | -32=-2a+6 | | 5+4y=34 | | 1/2(c+1)=5 | | −3/1=j/4−3/10 | | 1=3+m/12 | | -5+10x=-2x+1 | | 5(2x+3)-x+8=13 | | −3/1=4j−3/10 | | -19x+5+12x=-3-7x+8 | | n÷13=11 | | 5(x)=4x-1 | | -9(x-6)=9x+108 | | |x|-10=-5 | | `-3x+15=-96` | | -11=4(w-8)+3w | | (x)=x^2+6x+14 | | -21=y/9 | | x-120=-120 | | x+17/4=10 | | 4x6=98 | | a/11+14=11 | | 2x²-6x+9=0 | | -17=5x+8(x+6) | | y=35(1)+70 | | |-4x-2|+3=9 | | u/3-10=25 | | 0.75(y+1)=-6 | | k/5+10=13 | | −4x+7=9−2x | | 36=8(y-6)+4y | | w=16÷4 |